Materials Design via Optimized Intramolecular Noncovalent Interactions for High-Performance Organic Semiconductors - Guo, Xiaojie; Liao, Qiaogan; Manley, Eric F; Wu, Zishan; Wang, Yulun; Wang, Weida; Yang, Tingbin; Shin, Young-Eun; Cheng, Xing; Liang, Yongye; Chen, Lin X; Baeg, Kang-Jun; et al. (Chemistry of materials, 2016)
We report the design, synthesis, and implemention in semiconducting polymers of a novel head-to-head linkage containing the TRTOR (3-alkyl-3′-alkoxy-2,2′-bithiophene) donor subunit having a single strategically optimized, planarizing noncovalent S···O interaction. Diverse complementary thermal, optical, electrochemical, X-ray scattering, electrical, photovoltaic, and electron microscopic characterization techniques are applied to establish structure–property correlations in a TRTOR-based polymer series. In comparison to monomers having double S···O interactions, replacing one alkoxy substituent with a less electron-donating alkyl one yields TRTOR-based polymers with significantly depressed (0.2–0.3 eV) HOMOs. Furthermore, the weaker single S···O interaction and greater TRTOR steric encumberance enhances materials processability without sacrificing backbone planarity. From another perspective, TRTOR has comparable electronic properties to ring-fused 5H-dithieno[3,2-b:2′,3′-d]pyran (DTP) subunits, but a centrosymmetric geometry which promotes a more compact and ordered structure than bulkier, axisymmetric DTP. Compared to monosubstituted TTOR (3-alkoxy-2,2′-bithiophene), alkylation at the TRTOR bithiophene 3-position enhances conjugation and polymer crystallinity with contracted π–π stacking. Grazing incidence wide-angle X-ray scattering (GIWAXS) data reveal that the greater steric hindrance and the weaker single S···O interaction are not detrimental to close packing and high crystallinity. As a proof of materials design, copolymerizing TRTOR with phthalimides yields copolymers with promising thin-film transistor mobility as high as 0.42 cm2/(V·s) and 6.3% power conversion efficiency in polymer solar cells, the highest of any phthalimide copolymers reported to date. The depressed TRTOR HOMOs imbue these polymers with substantially increased I on/I off ratios and V oc’s versus analogous subunits with multiple electron donating, planarizing alkoxy substituents. Implementing a head-to-head linkage with an alkyl/alkoxy substitution pattern and a single S···O interaction is a promising strategy for organic electronics materials design.